HAK INGKAR NOTARIS SEBAGAI SAKSI DALAM PERADILAN PIDANA - Arum Dewi Azizah Salsabila; Suhariningsih Suhariningsih; Ismail Navianto (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2018)
the purpose of this study was to find out why the notary right of refusal can not be used in criminal justice and what are the legal implications of a notary if a notary becomes a witness in a criminal court. This research uses normative juridical research method with the approach of legisla- tion, conceptual, historical, case. The notarization rights can not be used in criminal justice because the criminal proofing system in Indonesia, the position of witness testimony in the search for truth materill, and the principle of examination of judge who directly and orally. As well as the legal implications arising from the right to a notary if the notary has been approved by the Notary Board of Honor (MKN) to appear as a witness in a criminal court that the notary’s right is void. DOI: http://dx.doi.org/10.17977/um019v3i12018p008